2018
DOI: 10.1016/j.marpolbul.2017.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of ocean warming on different components of plant-herbivore interactions

Abstract: There is increasing uncertainty of how marine ecosystems will respond to rising temperatures. While studies have focused on the impacts of warming on individual species, knowledge of how species interactions are likely to respond is scant. The strength of even simple two-species interactions is influenced by several interacting mechanisms, each potentially changing with temperature. We used controlled experiments to assess how plant-herbivore interactions respond to temperature for three structural dominant ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 80 publications
(92 reference statements)
3
31
0
Order By: Relevance
“…It is considered to be a key herbivore, due to its major role in structuring and controlling macroalgal assemblages that are themselves an important habitat for many species . Western Mediterranean populations were also reported to die at temperatures above 29°C, and to decline in performance in values just below it (Pag es et al 2017). In a previous study, we reported a thermal threshold of~30.5°C, above which sea urchin mortality increases dramatically, indicating that the recent rapid warming along the Israeli coast may play a role in its population collapse on the southeastern Mediterranean reefs (Yeruham et al 2015).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is considered to be a key herbivore, due to its major role in structuring and controlling macroalgal assemblages that are themselves an important habitat for many species . Western Mediterranean populations were also reported to die at temperatures above 29°C, and to decline in performance in values just below it (Pag es et al 2017). In a previous study, we reported a thermal threshold of~30.5°C, above which sea urchin mortality increases dramatically, indicating that the recent rapid warming along the Israeli coast may play a role in its population collapse on the southeastern Mediterranean reefs (Yeruham et al 2015).…”
Section: Introductionmentioning
confidence: 78%
“…In a bioinvasion context, effective invasive consumers might compete for resources with native consumers and thereby reduce their survivability and reproduction potential (Simberloff 2005). However, this combined scenario has rarely been experimentally tested (Pag es et al 2017). However, this combined scenario has rarely been experimentally tested (Pag es et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We used P. oceanica as a food resource since it is easy to control and measure in consumption experiments (Pagès et al. ), and the objective of this experiment was merely to confirm if predator non‐consumptive effects on prey feeding behavior existed. Leaves were removed after 7 d, and the total area consumed was estimated using a ruler.…”
Section: Methodsmentioning
confidence: 99%
“…In both trials, experimental sea urchins were provided four 5 9 1 cm pieces of the seagrass Posidonia oceanica (a common food for this species) that had been cleaned of epibionts. We used P. oceanica as a food resource since it is easy to control and measure in consumption experiments (Pag es et al 2017), and the objective of this experiment was merely to confirm if predator nonconsumptive effects on prey feeding behavior existed. Leaves were removed after 7 d, and the total area consumed was estimated using a ruler.…”
Section: Size-mediated Predator Non-consumptive Effectsmentioning
confidence: 99%
See 1 more Smart Citation